Simplifying
10x + -8 = ax + b
Reorder the terms:
-8 + 10x = ax + b
Solving
-8 + 10x = ax + b
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-1ax' to each side of the equation.
-8 + -1ax + 10x = ax + -1ax + b
Combine like terms: ax + -1ax = 0
-8 + -1ax + 10x = 0 + b
-8 + -1ax + 10x = b
Add '8' to each side of the equation.
-8 + -1ax + 8 + 10x = 8 + b
Reorder the terms:
-8 + 8 + -1ax + 10x = 8 + b
Combine like terms: -8 + 8 = 0
0 + -1ax + 10x = 8 + b
-1ax + 10x = 8 + b
Reorder the terms:
-8 + -1ax + -1b + 10x = 8 + b + -8 + -1b
Reorder the terms:
-8 + -1ax + -1b + 10x = 8 + -8 + b + -1b
Combine like terms: 8 + -8 = 0
-8 + -1ax + -1b + 10x = 0 + b + -1b
-8 + -1ax + -1b + 10x = b + -1b
Combine like terms: b + -1b = 0
-8 + -1ax + -1b + 10x = 0
The solution to this equation could not be determined.